2016
DOI: 10.18632/oncotarget.10709
|View full text |Cite
|
Sign up to set email alerts
|

MYCN promotes neuroblastoma malignancy by establishing a regulatory circuit with transcription factor AP4

Abstract: Amplification of the MYCN oncogene, a member of the MYC family of transcriptional regulators, is one of the most powerful prognostic markers identified for poor outcome in neuroblastoma, the most common extracranial solid cancer in childhood. While MYCN has been established as a key driver of malignancy in neuroblastoma, the underlying molecular mechanisms are poorly understood. Transcription factor activating enhancer binding protein-4 (TFAP4) has been reported to be a direct transcriptional target of MYC. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 49 publications
4
22
0
Order By: Relevance
“…We further validated synthetic lethality of TFAP4 with MYCN amplification in vitro and in vivo in a range of neuroblastoma cell lines. Our results are consistent with those of Xue et al [ 33 ], who reported that silencing of TFAP4 inhibited proliferation of MYCN -expressing cell lines in vitro.…”
Section: Discussionsupporting
confidence: 93%
“…We further validated synthetic lethality of TFAP4 with MYCN amplification in vitro and in vivo in a range of neuroblastoma cell lines. Our results are consistent with those of Xue et al [ 33 ], who reported that silencing of TFAP4 inhibited proliferation of MYCN -expressing cell lines in vitro.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, LAPTM4B was shown to also regulate AP4 expression via its effects on c‐myc, resulting in a circular positive feedback loop. Although some research has shown that c‐myc works together with AP4 to regulate tumour pathogenesis (Xue et al ., ) or that AP4 regulates the Wnt signalling pathway (Lebensohn et al ., ), which also involves c‐myc, our report is the first to show that AP4 also regulates c‐myc by affecting LAPTM4B expression. As summarized in Fig.…”
Section: Resultssupporting
confidence: 56%
“…TFAP4 belongs to the basic helix-loop-helix-leucine zipper (bHLH-LZ) subgroup of proteins and recognizes the symmetrical DNA core sequence CAGCTG 34 , 35 . Overexpression of TFAP4 promotes neuroblastoma cell growth 36 and induces the epithelial-mesenchymal transition (EMT) and metastasis in colorectal cancer 32 . Importantly, it is believed that TFAP4 is involved in maintaining cancer cells in a progenitor-like state 25 , which confers a degree of tumor stemness.…”
Section: Discussionmentioning
confidence: 99%